A Short Note on the ATP Fund of Denmark - Vittas, Dimitri (World Bank, Washington, DC, 2012)
The Danish ATP (Arbejdmarkedets TillaegsPension or Labor Market Supplementary Pension) fund is a public pension fund that was created in 1964 to complement the universal pension benefit that is financed from general tax revenues and is paid to all old-age residents. When it was created, participation in ATP was compulsory on most working people. But over the last decade or so compulsory coverage has been expanded to most recipients of transfer income. Contribution amounts are set in absolute terms, but are low relative to earnings (less than 1 percent of average earnings). ATP has benefited from scale economies and compulsory worker participation and has been able to operate with high efficiency and low costs. Its investment performance has been uneven over the years, reflecting the applied investment policies and rules as well as prevailing financial conditions. In recent years, it has been a leader among Danish pension institutions in adopting innovative investment policies and has enjoyed an enviable record of high investment returns and low operating costs. In addition, it has long offered deferred group annuities with guaranteed benefits and periodic bonuses (with profits policies). However, ATP also suffers from several weaknesses and shortcomings. It has a cumbersome governance structure, rooted in labor market relations and the role of social partners, while its group annuities have been based on rather 'idiosyncratic' risk-sharing arrangements. Nevertheless, it took the lead in using long-dated interest-rate swaps in euro markets and recently created a department that specializes in hedging its pension liabilities. And it is in the process of adopting a new plan for guaranteed benefits that aims to enhance the management of both investment and longevity risks.